2016
DOI: 10.1126/science.aaf5327
|View full text |Cite
|
Sign up to set email alerts
|

Radical SAM catalysis via an organometallic intermediate with an Fe–[5′-C]-deoxyadenosyl bond

Abstract: Radical SAM enzymes use a [4Fe-4S] cluster to cleave S-adenosylmethionine (SAM) to initiate diverse radical reactions. These are thought to involve the 5′-deoxyadenosyl radical intermediate, which has not yet been detected. Here we rapid freeze-quench trap a catalytically competent intermediate in the reaction catalyzed by the radical SAM enzyme pyruvate formate-lyase activating enzyme. Characterization of the intermediate by electron paramagnetic resonance and 13C, 57Fe electron-nuclear double resonance spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
190
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(202 citation statements)
references
References 39 publications
12
190
0
Order By: Relevance
“…Our studies here thus have revealed that the [4Fe-4S] cluster in a radical SAM enzyme can be tuned to cleave any one of the three bonds to the sulfonium sulfur of SAM or analogues. Together with recent studies on PFL-AE and Ph Dph2, 17,29 our study provides compelling evidence for the versatility of these [4Fe-4S] clusters.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Our studies here thus have revealed that the [4Fe-4S] cluster in a radical SAM enzyme can be tuned to cleave any one of the three bonds to the sulfonium sulfur of SAM or analogues. Together with recent studies on PFL-AE and Ph Dph2, 17,29 our study provides compelling evidence for the versatility of these [4Fe-4S] clusters.…”
supporting
confidence: 81%
“…This intermediate, could be compared to the catalytic organometallic intermediate in pyruvate formate lyase-activate enzyme (PFL-AE). 17 Both intermediates are formed by substrate (SAM or SAM analogue) cleavage with bonding of the nascent radical/cleavage product to the [4Fe-4S] cluster, with the difference being whether the Fe or the S atom in the cluster is directly bonded.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11,19 However, similar organometallic complex had not been demonstrated for RS enzymes until very recently, when the [4Fe-4S] 2+ cluster of the RS enzyme, pyruvate formatelyase activating enzyme is shown to react with the 5′-dA• to form a highly reactive organometallic intermediate. 20 This study and our current result suggest that the unique iron of [4Fe-4S] clusters in RS enzymes can readily form a C-Fe complex. Such a property not only may help to explain the unusual chemistries catalyzed by the [4Fe-4S]-containing RS enzymes, but also may open up new avenues to tune the activity or develop new chemistry for this enzyme class or for other [4Fe-4S]-containing enzymes.…”
supporting
confidence: 64%
“…Figure S1). 12 Liu and coworkers showed that the H4′ atom of 1 is abstracted by 5′-dAdo• to give 5′-deoxyadenosine (5′-dAdo) as one of products in addition to the dehydrated product (Figure 2). 6 The reaction of AprD4/AprD3 with 1, 2, kanamycin C (3) and kanamycin B (4) produced similar amounts of 5′-dAdo, whereas only a small amount of 5′-dAdo was detected with 2′-N-acetylparomamine (5) and paromomycin (6) (Figure 3 and Table 1).…”
Section: Enzyme Reaction In the Presence Of Deuterium Oxidementioning
confidence: 99%